BODILOPSIS OGLOBLINI (SEMENOV ET SI MEDVEDEV, 1928) (COLEOPTERA, SCARABAEIDAE, APHODIINAE) – A CIRCUMCASPIAN SPECIES - G. M. Abdurakhmanov; I. V. Shokhin (Юг России: экология, развитие, 2016)
Bodilopsis ogloblini (Semenov et Medvedev, 1928) comb.n. (previously included in the subgenera Mendidius and Bodilus of the genus Aphodius) are recorded as new for the fauna of Dagestan, Azerbaijan, the Caucasus and Russia. This species belongs to a subgenus Bodilopsis and is close to widely distributed species: B. sordidus (Fabricius, 1775) and B. rufus (Moll, 1782). B. ogloblini differs from all close species first of all by color of certain parts: dark (from dark-brown to black) antennal club, black head (sometimes clypeal margins a little lighter, darkbrown) and dark-brown abdomen. All species mentioned above have light antennal club (often yellow, sometimes brownish), head light (from yellow to red-brown) or light with dark-brown maculae, abdomen also light (from yellow to reddish, sometimes brownish). Coarse, rugose clypeal sculpture (without distinct punctation) is typical for B. ogloblini. Other species have more or less densely roughly punctured clypeus, never rugose. Besides new species differs from species of the Alocoderus by not framed anterior pronotal margin and by mostly black (sometimes dark-brown) pronotum (in A. hydrochaeris and A. digitalis anterior pronotal margin distinctly framed; pronotum in A. digitalis yellow, in A. hydrochaeris – yellow with brown spot in the middle). B. ogloblini also differs from A. sordidus by shining punctured elytral apices (in B. sordidus elytral apices distinctly shagreened, mat, without punctation). It differs from B. rufus by normal sharp lower spur of middle male tibia (male of A. rufus with modified lower spur of middle tibia, truncated at apex).